Impact assessment of multipurpose artificial insemination technicians in rural India training for rural youth pathway for self-employment - VERMA, ATUL KUMAR; PRATAP, JITENDRA; TRIPATHI, ASHUTOSH; PATEL, AKHIL; SHUKLA, MANISH KUMAR; SINGH, VIJAY; KHAN, MOHD. AMEER; SACHAN, VIKAS; TYAGI, KULDEEP KUMAR; GUPTA, RATAN (The Indian Journal of Animal Sciences, 2025)
The present study was carried out on 146 Multipurpose Artificial Insemination Technician in Rural India (MAITRI) trainees at the College of Veterinary and Animal Sciences, Sardar Vallabhbhai Patel University of Agriculture and Technology, Meerut, during 2021–2024. The respondents represented Western, Eastern, and Central regions of Uttar Pradesh. The findings revealed that the majority of respondents were Hindu (91.10%), belonged to the OBC category (54.10%), were relatively young (53.42%), and had limited professional experience (84.93%) in artificial insemination (A.I.). Despite facing several challenges–such as economic constraints, logistical issues, and lack of advanced technologies–most respondents reported that A.I. services and semen quality were adequate to achieve conception rates within the expected level (30–40%). The majority of respondents (72.60%) performed a relatively low number of inseminations (0–6 animals) per day, usually alongside their primary treatment activities, which contributed to lower daily income from this profession in their area. The chi–square test analysis showed a highly significant association between the three regions of Uttar Pradesh (Western, Eastern, and Central) and several parameters, including number of A.I. performed per day, average daily income, number of inseminations using sex–sorted semen per week, income from other sources, distance covered per day, and utilization of liquid nitrogen. A significant association (P ≤ 0.05) was also observed with average daily expenditure. However, parameters such as landholding capacity and work experience were found to be non–significant.